Strategies for the Protection of Landmine Victims; A Restorative Justice Approach - Mohamadi, Farshad (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2025)
In the current context of criminal law, the rehabilitation and compensation of those affected by landmines pose significant difficulties that require a creative and comprehensive approach. The research paper, titled "Strategies for the Protection of Landmine Victims: A Restorative Justice Approach," aims to investigate and outline effective strategies that go beyond traditional punitive legal systems. Instead, the paper seeks to incorporate the principles of restorative justice into the rehabilitation of landmine victims. This study aims to examine current legal mechanisms and their limitations in effectively addressing the complex needs of victims. It endeavours to identify restorative practices that prioritize healing, compensation, and the reintegration of victims into society. By doing so, it intends to ensure the protection and well-being of victims. This paper presents a comprehensive model that utilizes restorative justice as a crucial instrument for safeguarding landmine victims. The model is supported by a variety of case studies, international legal precedents, and theoretical frameworks. This text critically analyzes the capacity of restorative justice to promote communication between victims and offenders, cultivate community backing, and enforce reparative actions that adequately tackle the physical, psychological, and socio-economic consequences of landmine injuries. The research discusses victim protection by using a multidisciplinary approach that includes legal analysis, victimology, and human rights advocacy. It aims to provide practical recommendations for policymakers, legal practitioners, and civil society organizations involved in the fight against landmines and the pursuit of justice and rehabilitation for the victims.